Physiotherapy Students' Use of Online Technology as part of their Learning Practices: A Case Study - M. Rowe; JM Frantz; V Bozalek (AOSIS, 2012)
The relevance of non-technical skills have long been acknowledged asimportant components of clinical learning, and there is evidence that integrating technologycan facilitate their development by encouraging reflection, and by enhancing communicationand reasoning. However, effectively integrating technology into learning practices must takethe contextual needs of students into consideration. The aim of this study was to determinewhat online tools undergraduate physiotherapy students at one South African university arefamiliar with, and how they use them as part of their learning practices.The case study was conducted in a university physiotherapy department in the WesternCape during 2010. A cross-sectional, descriptive design used a survey to obtain quantitativeand qualitative data from participants, and a pilot study was conducted to test the reliability of the instrument. All ethicalconsiderations were adhered to.Seventy six percent of participants had access to the internet at home, and 93% of them belonged to a social network, althoughfewer than half used it for their studying. Few students reported using the internet for more than information retrieval but reportedwanting to use it for enhanced communication with lecturers. Almost all respondents believed that lectures were a useful way tolearn. However, 61% added that integrating online learning activities with lectures could have value.Integrating technology into healthcare education has the potential to develop non-technical skills that are relevant for clinicalpractice. However, this group of students currently lack the experience and insight to use technology effectively as part of theirlearning practices. Educators must take cognisance of the educational and contextual needs of students if they wish to integratetechnology into clinical teaching.